Uji sitotoksisitas dan antiproliferatif ekstrak etanol daun leunca (Solanum Nigrum,L) terhadap sel raji - Rahma Dona; Nanik Sulistyani; Laela Hayu Nurani (Pharmaciana, 2016)
Leunca (Solanum nigrum,L.) is one of the medicinal plant which used society for traditional medication as antipyretic, hypotensive and anticancer. The aim of  this research was to know an anticancer activity of ethanol extract of leunca leaves, emphasized on an ability to inhibit the growth Raji cell. Ethanol extract took from leunca leaf powder that epitomized using ethanol solvent by Soxhlet instrument. Citotoxicity test was done by incubating Raji cell at a density of 2x104 with treatment using ethanol extract from leunca (Solanum nigrum L.) leaf in several concentration 500; 250; 125; 62,5; 31,25; 15,62; 7,81 and 3,90 µg/ml. A test was done by MTT method and the percent of cell mortality was calculated. The LC50 values were calculated using probit analysis. The research continued with antiproliferation test on treatment sample concentration 50; 25 µg/ml with cell control for 24, 48, and 72 hours.The result of research indicate that ethanol extract of leunca leaves had cytotoxic effect towards Raji cell with LC50 values 59,22 µg/ml. The result of  antiproliferation test showed that there were the growth of inhibitation on treatment sample with doubling time values 69,56 hour at concentration 50 µg/ml; 60,00 hour at concentration 25 µg/ml, and doubling time cell control is 44,98 hour.